Exploring barriers to the use of formal maternal health services and priority areas for action in Sidama zone, southern Ethiopia - Aschenaki Z. Kea; Olivia Tulloch; Daniel G. Datiko; Sally Theobald; Maryse C. Kok (BMC, 2018)
Abstract Background In 2015 the maternal mortality ratio for Ethiopia was 353 per 100,000 live births. Large numbers of women do not use maternal health services. This study aimed to identify factors influencing the use of maternal health services at the primary health care unit (PHCU) level in rural communities in Sidama zone, south Ethiopia in order to design quality improvement interventions. Methods We conducted a qualitative study in six woredas in 2013: 14 focus group discussions (FGDs) and 44 in-depth interviews with purposefully selected community members (women, male, traditional birth attendants, local kebele administrators), health professionals and health extension workers (HEWs) at PHCUs. We digitally recorded, transcribed and thematically analysed the interviews and FGDs using Nvivo. The 'three delay model' informed the analytical process and discussion of barriers to the use of maternal health services. Results Lack of knowledge on danger signs and benefits of maternal health services; cultural and traditional beliefs; trust in TBAs; lack of decision making power of women, previous negative experiences with health facilities; fear of going to an unfamiliar setting; lack of privacy and perceived costs of maternal health services were the main factors causing the first delay in deciding to seek care. Transport problems in inaccessible areas were the main contributing factor for the second delay on reaching care facilities. Lack of logistic supplies and equipment, insufficient knowledge and skills and unprofessional behaviour of health workers were key factors for the third delay in accessing quality care. Conclusions Use of maternal health services at the PHCU level in Sidama zone is influenced by complex factors within the community and health system. PHCUs should continue to implement awareness creation activities to improve knowledge of the community on complications of pregnancy and benefits of maternal health services. The health system has to be responsive to community's cultural norms and practices. The mangers of the woreda health office and health centres should take into account the available budgets; work on ensuring the necessary logistics and supplies to be in place at PHCU.